John Cook Wilson on the indefinability of knowledge - Longworth, Guy; Wimmer, Simon (Technische Universität Dortmund, 2022)
Can knowledge be defined? We expound an argument of John Cook Wilson's that it cannot. Cook Wilson's argument connects knowing with having the power to inquire. We suggest that if he is right about that connection, then knowledge is, indeed, indefinable.
European journal of philosophy;30(4)
Keywords: 100